Faktor-faktor yang Berhubungan dengan Status Gizi Lebih /Obesitas pada Remaja Siswa SMA Negeri di Kota Pekanbaru - Ervira Dwiaprini As Syifa; Ratna Djuwita (Jurnal Kesehatan Komunitas, 2023)
Based on the 2013 and 2018 Basic Health Research, there was an increase in the prevalence of overnutrition and obesity in Riau province from 3.1% to 11.6%. This study aimed to analyze the factors associated with the incidence of overweight/obesity in adolescent students of public high schools in Pekanbaru City in 2023. The type of research is quantitative analytic with a cross-sectional design. The research was conducted in May-June 2023. Samples were class X and XI students in three high schools in Pekanbaru City, namely SMAN 4, SMAN 6, and SMAN 12. Sampling was done by purposive sampling. Independent variables were gender, adolescent knowledge, parental education, parental occupation, pocket money, parental obesity status, physical activity, sleep quality, fast food consumption, and sugary drink consumption. The dependent variable was overweight/obesity. Data were analyzed univariately, bivariate, and multivariate. The results showed that the dominant variable associated with overweight/obesity was parental obesity status (OR=3.12; 95% CI: 1.25-7.83). Adolescents with obese parents were three times more likely to experience overweight/obesity compared to adolescents who did not have obese parents. Other associated variables were student knowledge (OR=2.62; 95% CI: 1.27-5.39) and sweet food habits (OR=2.34; 95% CI: 1.04-5.27). For this reason, schools are expected to work with the Health Office and Community Health Center to organize counseling or seminars on nutrition and obesity in adolescents; schools can provide healthy canteens by limiting the availability of fast food and sugary drinks.